Democratization in the Arab world : prospects and lessons from around the globe - Miller, Laurel (Laurel E.) (Rand Corporation monograph series., 2012)
"Daunting challenges lie ahead for Arab countries where revolutions have upended longstanding authoritarian regimes. These unexpected events created new uncertainties in a troubled region: Would the Arab Spring lead to a flowering of democracy? Would loosening of the political systems in these countries unleash dangerous forces of extremism or ethno-sectarian conflict? Would new autocrats replace the old ones? Through a comparative analysis of past democratization experiences throughout the world over nearly four decades and a detailed look at recent uprisings in the Arab world, Democratization in the Arab World aims to help policymakers understand the challenges ahead, form well-founded expectations, shape diplomatic approaches, and take practical steps to foster positive change. The monograph explores the conditions and decisions that are most likely to influence whether democratization succeeds in Arab countries undergoing political transitions. It identifies the main challenges to democratization in these countries; analyzes how countries in Europe, Latin America, Asia, and Africa have dealt with similar challenges in the past; and suggests what the United States and broader international community can do to help strengthen fledgling democracies in the Arab world."--Page 4 of cover